Reconstruction of Human Rights Protection in the Criminal Justice Process Based on the Modern Criminal Law Paradigm in Indonesia - Marsudin Nainggolan (Politeknik Siber Cerdika Internasional, 2026)
Background: Human Rights (HAM) protection in the criminal justice system is a primary indicator of the legitimacy of a modern rule-of-law state. Indonesia has normatively adopted the principle of due process of law through the 1945 Constitution, the Criminal Procedure Code (KUHAP), and international human rights instruments such as the International Covenant on Civil and Political Rights (ICCPR). However, in practice, various human rights violations are still found, particularly during the investigation and evidentiary stages. Objective: This research aims to reconstruct a model of human rights protection based on the modern criminal law paradigm. Methods: The method used is normative juridical research employing statutory, conceptual, and case approaches. Results: The results show that human rights protection in Indonesia remains procedural rather than substantive. Therefore, an integrative model is needed that combines the legal theories of Hart and Dworkin, as well as the restorative justice approach. Conclusion: The findings demonstrate that an integrative model combining the exclusionary rule, pretrial reform, and restorative justice grounded in the legal theories of Hart and Dworkin constitutes the most viable framework for achieving substantive human rights protection in Indonesia’s criminal justice system.